Entre a espera e a esperança: experiências dos sertanejos na Hospedaria Getúlio Vargas, participações em movimentos sociais e migração para diversas paragens (Ceará, 1942-1959) - Monteiro, Renata Felipe (2025)
This thesis aims to reflect on the multiple experiences lived by the sertanejos inside and outside the Hospedaria Getúlio Vargas (Fortaleza), between 1942 and 1959. A shelter built during the Second World War, together with other shelters and hostels in the North and Northeast, the purpose of which was to quickly send thousands of northeasterners to the Amazon for rubber extraction. However, in order to make this crossing agile, several institutions collaborated. The problems faced by the migrants in these spaces, however, were many: lack of infrastructure, restriction of freedom, illness, death, etc. And the stay, which should have been brief, sometimes lasted quite long. Thus, these shelters were called “waiting territories”. This concept is also attributed to the hostels built in the late 19th and early 20th centuries, which primarily received foreign immigrants but which, during periods of drought (1877-78, 1889, 1915), received several people from Ceará. We had an initial discussion based on a well-established theoretical framework and a variety of documents, such as reports, newspapers and testimonies. At the end of the world conflict in 1945, the project to relocate the sertanejos was interrupted, with the discontinuation of the hostels and the development of other projects. However, the Hospedaria Getúlio Vargas only resumed its original activities - providing temporary shelter for people in transit - in 1951, becoming the main place to welcome the migrants. However, due to the lack of funds and government neglect, the sertanejos experienced moments of tension in that place. While they waited (for food and tickets), they moved around the city in search of public charity or to request measures from the government. When there was no negotiation between the agents of power and the sertanejos, the latter participated in social movements, such as hunger marches, riots, revolts, among other mass actions. In addition, they got involved with other political groups (workers, politicians and students) to fight against the high cost of living, the abusive price of transportation and for other rights. Finally, we sought to understand the migration trajectories of some sertanejos, whose stories were revealed in newspapers or through academic research. These individuals usually had no choice about where they would move to during the interim period of 1951-1953 and, especially, between 1958-59, as occurred in the so-called “Operação Flagelados”. Based on diverse documentation, including newspapers, reports, testimonies, official documents, among others, we seek to understand how these country folk experienced and faced the difficulties that existed at the Hospedaria Getúlio Vargas, how they moved around the city and got involved with other subjects, seeking to be protagonists of their own destinies.